ESG importance for long-term shareholder value creation: Literature vs. practice - Ilze Zumente; Jūlija Bistrova (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This article aims to detect how ESG adds value to the long-term shareholder value creation and to discover whether businesses are aware of positive ESG effects and, therefore, whether they will become more ESG-conscious. By conducting a qualitative content analysis on the academic literature, this article firstly aims to determine if shareholders' value is positively affected by corporate ESG awareness. Secondly, to test whether companies are becoming more conscious about the importance of ESG, the mission statements of publicly listed Central and Eastern European (CEE) companies are compared to their decade-old versions. This analysis allows us to conclude on whether companies have shifted their attention to the ESG factors as a part of their purpose of existence and, therefore, for long-term shareholder value creation, which is one of the main goals of the exchange-listed enterprises. The content analysis results show that companies with higher sustainability awareness ensure shareholder value creation via improved financial performance, management quality as well as reduced risk metrics. Additionally, qualitative nonfinancial factors such as reputation, stakeholder trust, employee satisfaction and engagement provide an even more significant effect on the long-term value than the pure financial matters. The theoretical trend is found to be supported by the fact that sustainability practice and consumer-oriented keywords dominate the mission statements of CEE companies, while keywords related to shareholders and profit experienced the most significant decrease from 2012 to 2021. The present research is unique as it looks at how companies tend to become more ESG aware, integrating the sustainability perspective into their mission statements in response to the global sustainability trend.
Keywords: 650; disclosures; CEE; ESG; firm value; shareholder value; sustainability